A novel 4-dimensional live-cell imaging system to study leukocyte-endothelial dynamics in ANCA-associated vasculitis - Catriona A. Walls; Neil Basu; Gayle Hutcheon; Lars P. Erwig; Mark A. Little; Dana Kidder (Taylor & Francis Group, 2020)
Neutrophils, monocytes and the endothelium are critical to ANCA-associated vasculitis (AAV) pathogenesis. This study aimed to develop a 4-dimensional (4D) live-cell imaging system that would enable investigation of spatial and temporal dynamics of these cells in health and disease. We further aimed to validate this system using autologous donor serum from AAV patients and polyclonal ANCA IgG, as well as exploring its potential in the pre-clinical testing of putative therapeutic compounds. Neutrophils and monocytes were isolated from peripheral venous blood of AAV patients or healthy controls and co-incubated on an endothelial monolayer in the presence of autologous serum. Alternatively, polyclonal ANCA IgG was used, following TNF-α priming, and imaged in 4-dimensions for 3 h using a spinning disc confocal microscope. Volocity 6.3® analysis software was used for quantification of leukocyte dynamics. The use of autologous serum resulted in increased neutrophil degranulation (p = .002), transmigration (p = .0096) and monocyte transcellular transmigration (p = .0013) in AAV patients. Polyclonal MPO-ANCA IgG induced neutrophil degranulation (p < .001) in this system. C5aR1 antagonism reduced neutrophil degranulation (p < .0002). We have developed a novel 4D in vitro system that allows accurate quantification of multiple neutrophil- and monocyte-endothelial interactions in AAV in a single assay. This system has the potential to highlight dynamics key to pathophysiology of disease, as well investigating the impact of potential therapeutics on these functions.